Concess\~oes e dinâmica regional: Um perfil dos deslocamentos pedagiados - Jean Marlo Pepino de Paula (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This paper discusses about the impact of the highway concession policy on regional income and dynamics. It gathers information from the 2010 Population census and a federal highway concession, the Autopista Fluminense, to examine the attenuation of per capita income in the potential commuting tolled. The discussion deducing that there is a high volume of regional commuting that potentially use the highway and not charged. Otherwise, there was a small portion of the population tariffed, how had lower incomes and charge with "gratuity" commuting. In addition, this study illustrate the impact and reflexes of the uni and bidirectional charges for this low-income population.
Keywords: H23; H41; J31; J61; L98; O18; 330; highway concessions; tolls; regional commuting; per capita income; transportation infrastructure